Measuring, Mapping, Creating: A mixed method approach to sedentary behaviours and work-place design - McGann, Sarah; Tye, Marian; Jancey, Jonine; Blackford, Krysten; Creagh, Robyn; Tollis, Leanne (The Architectural Science Association (ANZAScA), 2013)
This paper reports on the formation and success of an innovative interdisciplinary research team formed to tackle a current critical challenge in our social, cultural and built environments. The challenge—that of sedentary behaviour and its relationship to workplace design—is somewhat familiar to researchers in health promotion but is less so to architectural researchers. The research team has been especially choreographed to include a diverse membership with different skills and expertise ranging from highly scientific to highly creative practices. The team consists of experienced researchers from the fields of architecture, health promotion and recreation and includes early career researchers, doctoral and undergraduate students. The mixed methods employed in this study reinforce the value of engaging critical creative practices with scientific analyses. The success of the partnership is demonstrated by being awarded the first ‘Healthway’ grant to an area outside of Health Sciences at Curtin University. In undertaking the research and engaging in interdisciplinary practices it was found that all parties built understandings and capacities in unexpected and enriching ways. Tackling a real world challenge, such as this, through the full spectrum of scientific, critical and creative means results in multifaceted creative solutions and outputs with wide dissemination opportunities.